EFFECT OF ORAL ADMINISTRATION OF BITTER EXTRA ON THE HISTOMORPHOLOGY OF THE CEREBELLUM (Journal of Biomedical Investigation, 2024)
Background: Bitter Extra is a brand of herbal product adjudged to be efficacious in the treatment of various ailments.Aim: This study is aimed at investigating the effect of Bitter Extra on the histomorphology of the cerebellum.Method: Sixteen adult male Wistar Rats with weight between 158-230g were used for this study and were divided into four groups (1,2,3 and 4) with four (4) rats in each group. Group 1 served as the control while groups 2, 3 and 4 were taken as the test groups. Group 2 was administered 1.35ml/kg (low dose), group 3 was administered 2.7ml/kg (Medium dose), Group 4 was administered 5.4ml/kg (High dose) of Bitter Extra through an orogastric tube for a period of four weeks while group 1 was given water and feed only. The rats were fed and administered these amounts of drugs daily with their weights recorded after a week interval for four weeks.Results: There were no significant changes (P>0.05) in the mean body weights of the rats in the test groups administered with Bitter Extra. However, in the histology of the cerebellum, rats in Group 4 showed increased proliferation of the Purkinje cell bodies into the molecular layer. Group 3 showed focal increase in Purkinje cell proliferation and hypertrophy of the Purkinje cell layer with pushing of the molecular layer, while Group 2 showed increased hypertrophy of Purkinje cell bodies and hyperplasia of cells in the granular layer.Conclusion: These finding suggest that consumption of Bitter Extra does not in any way affect the body weight. High dosage consumption of Bitter Extra may cause hyperplasia, hypertrophy of the cells of the cerebellum which may lead to observable cerebellar dysfunction features.
Keywords: Bitter Extra; Body Weight; Cerebellum; Rats; Cerebellar Dysfunction